Resposta do tomate cereja sob cultivo orgânico aos níveis de água e diferentes tipos de cobertura morta - Silva, Valsérgio Barros da (2017)
Studies on the production of irrigated organic cherry tomatoes in the semi-arid region are still incipient, regarding the aspect of adequate irrigation management, especially in the case of the water crisis in the State of Ceará, with rains in the last few years below average and reserves ending up of water. In this sense, the present work had as objective the technical and economic evaluation of the effect of the different irrigation slides and soil cover on the cherry tomato production, from August 2016 to January 2017. The experiment was carried out in an área belonging to the Education Program in cooperative cells - (PRECE), in the municipality of Pentecoste. Conducted in randomized blocks, with three replications and subdivided plots, comprised of five primary treatments in the plots and three secondary treatments arranged in the subplots.The primary treatments consisted of five irrigation levels with 50, 75, 100, 125 and 150% of evapotranspiration of the culture for localized irrigation (ETcloc) and three secondary treatments consisting of two soil coverages, bagana de carnauba (BC) and elephant grass EC; In addition to a control treatment, soil without cover.The water used for irrigation came from a shallow well located on the banks of the Canindé River.The crop was irrigated by a drip irrigation system.The results obtained allowed us to conclude that an area of around 0.5 ha is necessary to guarantee sufficient income for the maintenance of each worker in the family.